Repeated MitraClip procedure in patients with recurrent MR after a successful first procedure: Limitations and outcome. (29th November 2017) - Curio, Jonathan; Reinthaler, Markus; Kasner, Mario; Al‐Hindwan, Haitham Saleh Ali; Baeckemo‐Johansson, Johan; Neumann, Tim; Jacobs, Stephan; Lauten, Alexander; Landmesser, Ulf
Abstract : Objectives: The present study aimed to evaluate the outcome and potential limitations of a repeated MitraClip procedure (ReClip). Background: The MitraClip procedure has emerged as a treatment option in high surgical risk patients suffering from severe mitral regurgitation (MR). However, despite successful initial repair a significant number of patients develops severe recurrent MR. Methods: Patients undergoing a ReClip procedure in our institution were retrospectively identified. Baseline data and the procedural outcome were assessed to identify potential limitations of such procedures. Results: Fifteen out of 234 patients undergoing a mitral‐valve repair with the MitraClip device (Abbott Vascular) underwent a ReClip due to recurrent MR. In 11 patients, a MR reduction of at least one degree without causing mitral valve stenosis (trans‐mitral mean gradient ≥5 mmHg) was achieved by performing a ReClip. After 1 year, two patients developed severe recurrent MR again. Pulmonary artery pressures significantly decreased after the procedure in individuals with successful repair (MR reduction of at least one degree and mitral valve mean gradient <5 mmHg). Conclusion: A ReClip procedure may be feasible in patients with recurrent MR but the risk benefit ratio should be carefully balanced against other treatment options.